SERUMPUN - Ade Saputra; Wimbrayardi Wimbrayardi; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2018)
Abstract The cultivation of this Serumpun's musical works is aimed to express musician musical experience in which compositional musics has inspired and gave the spirit of musician to learn music. On working on this musical work, musician presents Minang and Malay music collaborations with new packaging form, so that the producer can give the description that there are many similarities and congregation of both cultures. This musical works presents the development of melody, rhythm, and timbre into other instruments in terms of produced music and the selection of its instruments, so that the work presented becomes more attractive and acceptable at this time. Keywords: Serumpun.